2012
DOI: 10.3762/bjoc.8.205
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolinium and amidinium salts as Lewis acid organocatalysts

Abstract: SummaryThe application of imidazolinium and amidinium salts as soft Lewis acid organocatalysts is described. These salts were suitable catalysts for the activation of unsaturated thioesters in a Diels–Alder reaction and in the ring opening of thiiranes and epoxides. The products were isolated in good yields. The mild catalysts did not cause desulfurization of the products containing a thiol or thiocarbonyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…1 H NMR spectra were acquired at r.t. on a Bruker Avance 500 (500 MHz) in deuterated solvents as stated. 13…”
Section: Paper Syn Thesismentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR spectra were acquired at r.t. on a Bruker Avance 500 (500 MHz) in deuterated solvents as stated. 13…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl 3 ): δ = 8.95 (s, 1 H, H3), 8.52 (s, 1 H, H10′′), 8.25 (d, J = 8.9 Hz, 2 H, H5′′, H4′′), 8.03 (d, J = 8.5 Hz, 2 H, H8′′, H1′′), 7.96 (ddd, J = 4.9, 1.8, 0.7 Hz, 1 H, H6′), 7.88 (d, J = 8.4 Hz, 1 H, H3′), 7.78 (ddd, J = 8.4, 7.4, 1.9 Hz, 1 H, H4′), 7.64 (ddd, J = 8.9, 6.6, 1.3 Hz, 2 H, H7′′, H2′′), 7.53-7.47 (m, 2 H, H6′′, H3′′), 7.06 (ddd, J = 7.4, 4.9, 0.6 Hz, 1 H, H5′), 6.07 (dd, J = 51.9, 15.2 Hz, 2 H, H1′′′), 4.72 (d, J = 5.1 Hz, 1 H, H5), 2.68 (ddd, J = 14.5, 9.5, 4.7 Hz, 1 H, H7), 2.38 (ddt, J = 14.9, 12.1, 4.9 Hz, 1 H, H6), 2.22-2.09 (m, 1 H, H6), 2.09-1.99 (m, 1 H, H7), 1.64 (s, 3 H, H11), 1.28 (s, 3 H, H10), 1.15 (s, 3 H, H9). 13 C NMR (126 MHz, CDCl 3 ): δ = 150.6 (C3), 150.0 (C2′), 148.2 (C6′), 140.3 (C4′), 131.3 (C4′′a, C4′′b), 131.2 (C9′′a, C8′′a), 130.8 (C10′′), 129.8 (C8′′, C1′′), 128.3 (C7′′, C2′′), 125.6 (C6′′, C3′′), 122.7 (C5′), 122.5 (C5′′, C4′′), 121.4 (C9′′), 113.5 (C3′), 74.0 (C1), 65.7 (C5), 48.0 (C1′′′), 41.8 (C8), 40.2 (C7), 32.0 (C6), 21.9 (C10), 17.1 (C9), 14.9 (C11). 1,8,8-trimethyl-4-(pyridin-2-yl)-2,4-diazabicyclo[3.2.1]oct-2-en-2-ium Bromide 13Amidine 9 (617 mg, 2.69 mmol) and di(naphthalen-1-yl)methyl bromide 15 (1.03 g, 2.96 mmol) in MeCN (5 mL) were refluxed for 16 h. The solvent was removed and the salt was purified by column chromatography (CH 2 Cl 2 -MeOH, 9:1).…”
Section: Paper Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral guanidine systems are another promising class of Lewis acidic (phase-transfer) catalysts 3638. In 2002 Nagasawa et al reported the use of the tartaric-acid-derived C 2 -symmetric pentacyclic guanidine derivative 82 (Scheme 22) as a powerful chiral catalyst for the benchmark alkylation of Schiff base 56 36.…”
Section: Chiral Phase-transfer Catalystsmentioning
confidence: 99%
“…Due to our interest in ionic liquids [ 4 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], we wanted to explore the catalytic oxidative behavior of tetrachloroferrate-based ionic liquids in the synthesis of a quinoline derivate. Quinoline derivates and quinoline itself are important structural units in a variety of biologically active natural products.…”
Section: Introductionmentioning
confidence: 99%